Bad cops : a Henry Christie thriller - Oldham, Nick, 1956- (Oldham, Nick, 1956- Detective Superintendent Henry Christie novel., 2017)
"Two murders, apparently unconnected: one victim shot to death in his office, the other brutally stabbed in what appears to have been a road rage incident...neither case solved. Six months later, following a desperate plea from a chief constable, Detective Superintendent Henry Christie finds himself travelling across the country to carry out an urgent review of the two killings. His investigations will plunge him into a terrifying world of murder and corruption and find him pitted against a well-organized group who seem to anticipate his every move. Henry Christie is about to discover just how bad some cops can be when their backs are against the wall.''--Book jacket